Disaster education in undergraduate nursing curriculum: A Delphi study to prioritise content for nursing students. Issue 5 (October 2022) - Ranse, Jamie; Ituma, Odira W.N.; Bail, Kasia; Hutton, Alison
Abstract: Background: When a disaster occurs, a health response must adapt to meet the needs of the community. Nursing students may be able to assist in supporting the nursing workforce to meet the community's health needs during and/or following a disaster. However, there is a paucity of literature regarding the educational needs of nursing students regarding disaster preparedness. Further, the disaster-related content that is important to be included in undergraduate nursing curricula is poorly understood. Methods: This study used a modified three-round Delphi design guided by the principles of the Guidance on Conducting and REporting DElphi Studies . Data was collected from Australian clinical and academic nurses via online surveys. Analysis was undertaken using descriptive statistics including means of central tendency, with disaster content topic areas and statements considered a priority if they obtained a mean score of four out of five, or greater. Results: A total of 38 nurses participated in this study. Across the three rounds, eight topic areas and 37 different statements were included. High priority statements for topic inclusions in undergraduate curricula were "disaster knowledge, " "assessment and triage, " "critical thinking, " and "technical skills." Additionally, statements relating to "mental wellbeing" and "teamwork in stressful situations" were ranked as the highest. Conclusions: Disaster-related content should be included in undergraduate nursing curricula. This content could be embedded within existing units of study and/or delivered as a standalone unit of study. The educational method for delivering disaster content could vary from a didactic approach to simulation exercises depending on the content and local context.